A new look on the teaching profession through the analasys of modern educational standards - Shevtsova M. A. (Interactive science, 2016)
The article discusses the ways of problem solving in the sphere of pedagogical education to prepare teachers for lifelong professional self-development. The analysis and fulfillment of requirements of modern educational standards help to solve the problem of training future teachers based on system-activity approach, using personal experience of students and modern technologies. The professional teacher standard - is the main point in improving the quality of education in training teachers.
Keywords: современные образовательные технологии; профессиональный стандарт педагога; развитие педагогического образования; ситуационный анализ; modern educational technologies; современные образовательные стандарты; modern educational standards; conception of development of pedagogical education support; professional teacher standard; case-study; концепция поддержки